Epidemiology and evolution of historical aspects of differential diagnostic criteria of abdominal pain syndrome by the example of acute pancreatitis (literature review) - A.A. Baulin; L.A. Averyanova; V.A. Baulin; O.A. Baulina (Известия высших учебных заведений. Поволжский регион: Медицинские науки)
The article provides an overview of domestic and foreign literature summarizing data on the dynamics of the incidence of acute pancreatitis. Based on databases elibrary.ru, RSCI, PubMed discusses approaches to the management of patients with abdominal pain syndrome using the example of acute pancreatitis. The data on the management of patients with abdominal pain, the mechanisms of its formation, and the causes of its occurrence are considered. The achievements and unresolved issues related to the early and differential diagnosis of this pathology are described, which requires the expediency of continuing scientific research in this area.